Dynamic modular vCPE orchestration in Platform as a Service architectures - Meneses, Flavio (2019)
This paper proposes a framework where Customer Premises Equipments (CPEs) are dynamically instantiated, by leveraging Software Defined Networking (SDN) and Network Function Vitualisation (NFV), in the cloud as a chain of containerised virtual network functions (VNFs). Resulting virtual CPE instances (i.e., vCPEs) are organised in clusters and a Management and Orchestrator (MANO) entity is used to monitor the cluster and to migrate vCPEs among the nodes composing the cluster as required for ensuring the load balancing of the resources of the cluster. During the vCPEs migration process, the data-path is dynamically updated via SDN mechanisms. A proof of concept prototype of the framework was developed and evaluated in an experimental testbed, showcasing its feasibility and a near-zero downtime while migration is taking place.